Unpacking the provision of the industrial commons in Industry 4.0 cluster - Götz, Marta (Economics and Business Review, 2019)
This paper argues that provision of industrial commons (IC), might be consideredas a crucial factor of a cluster’s attractiveness in digital transformation, e.g. inIndustry 4.0 (I4.0) time. By drawing on the qualitative case study method of HamburgAviation cluster (HAv), it aims at exploring the nature of IC in the leading GermanI4.0 cluster. Proximity emerges, even if sometimes not explicitly, as the recurring topicfacilitating the provision of IC, along with the advancement of I4.0. As Industry 4.0stipulates much uncertainty, the closeness featuring in clusters, seems to bring variousbenefits, which can help address challenges associated with I4.0, and faced mainly bysmall and medium firms (SMEs). The vicinity to key actors and the gains of networking,reflect the importance of (un)articulated proximity